Low‐cost modified‐atmosphere hermetic storage structures to reduce storage losses of maize (Zea mays L.) cobs and sorghum (Sorghum bicolor L.) heads. (3rd December 2019) - Tola, Yetenayet B; Muleta, Obsuman D; Hofacker, Werner C
Abstract: BACKGROUND: Production and marketing of cereal grains are some of the main activities in developing countries to ensure food security. However, the food gap is complicated further by high postharvest loss of grains during storage. This study aimed to compare low‐cost modified‐atmosphere hermetic storage structures with traditional practice to minimize quantitative and qualitative losses of grains during storage. The study was conducted in two phases: in the first phase, seven hermetic storage structures with or without smoke infusion were compared, and one selected structure was further validated at scaled‐up capacity in the second phase. RESULTS: Grains stored in PVC bag‐supported structures (with or without smoke infusion) resulted in low live weevil population, low percentage of damaged grains and reduced weight loss with better retention of crude protein and fat contents. Results from validation study also demonstrated that maize and sorghum stored in improved storage structures experienced, respectively, 9.8% and 10.4% weevil damage as compared with 47.3% and 42.3% when stored in traditional storage structures. The same was true in terms of crude protein and fat contents. Conclusions: The study demonstrated that storage structures supported with PVC bags are efficient and low‐cost structures for reducing storage‐related losses and supporting food security efforts as compared to traditional methods. Furthermore, the bags can be made locally and with various storage capacities to store either shelled or unshelled products. © 2019 Society of Chemical Industry